Cancer treatment decisions for people living with dementia: Experiences of family carers, a qualitative interview study - Catherine Hynes; Victoria J. Hodges; Lynda Wyld; Caroline Mitchell (Wiley, 2022)
Abstract Background As the UK population ages, the prevalence of both dementia and cancer will increase. Family carers of people with dementia who are subsequently diagnosed with cancer are often involved in treatment decisions about cancer. These decisions are uniquely challenging. Objectives To explore the experience of carers involved in cancer treatment decisions for people with dementia. Design A cross‐sectional qualitative interview study with inductive thematic analysis. Setting and Participants Sixteen carers of people with dementia were identified via Primary Care Research Networks and the Join Dementia Research database. Results Three main themes were derived: 'already at breaking point', which describes the extreme strain that carers were already under when the cancer diagnosis was made; 'maintaining the status quo', which describes how despite the gravity of a cancer diagnosis, avoiding further dementia‐related deterioration was of prime importance; and 'LPA', which explores the benefits and frustrations of the use of lasting powers of attorney. Discussion Current services are ill‐equipped to deal with people who have a combination of dementia and cancer. Proxy decisions about cancer care are made in the context of carer stress and exhaustion, which is exacerbated by shortcomings in service provision. Conclusions As the prevalence of comorbid cancer and dementia rises, there is an urgent need to improve services that support carers with proxy health care decision‐making. Patient or Public Contribution The study design was codeveloped with a local dementia‐specific patient and public involvement (PPI) group. A project‐specific PPI group was formed with support from the Alzheimer's Society Research Partnership scheme to provide further bespoke input.